2016
DOI: 10.1084/jem.20151519
|View full text |Cite
|
Sign up to set email alerts
|

Radical cure of experimental babesiosis in immunodeficient mice using a combination of an endochin-like quinolone and atovaquone

Abstract: Human babesiosis is a tick-borne multisystem disease, and current treatments have both adverse side effects and a significant rate of drug failure. Lawres et al. report that endochin-like quinolones, in combination with atovaquone, cure experimental babesiosis in immunodeficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 49 publications
10
103
0
Order By: Relevance
“…with 10 6 B. microti-infected RBCs. As a control, another group of 5 BALB/c females were injected with B. microti-infected erythrocytes but also were subjected to combination therapy (atovaquone plus ELQ-334, 10 mg/kg each, daily for 7 days starting at day 4 postinfection), as described previously (20). Smears, serum samples, and plasma samples were collected prior to infection and every 4 days postinfection for 42 days.…”
Section: Methodsmentioning
confidence: 99%
“…with 10 6 B. microti-infected RBCs. As a control, another group of 5 BALB/c females were injected with B. microti-infected erythrocytes but also were subjected to combination therapy (atovaquone plus ELQ-334, 10 mg/kg each, daily for 7 days starting at day 4 postinfection), as described previously (20). Smears, serum samples, and plasma samples were collected prior to infection and every 4 days postinfection for 42 days.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the mechanism by which these drugs exert their anti- Babesia activity has only recently begun to be elucidated. Recent studies using a short-term in vitro culture as well as immunocompromised mice have shown that, of the four drugs used for treatment of human babesiosis, only atovaquone shows efficacy against the parasite in mouse red blood cells both in vitro and in vivo 11. These results, along with the shortcomings of available diagnostic tools to distinguish between past and active infection to prevent transfusion-transmitted babesiosis, have stimulated efforts to improve therapies and diagnostics111213141516171819.…”
mentioning
confidence: 99%
“…The Lys228-Met substitution in S. cerevisiae, which is analogous to position 222 in the T. gondii cytochrome b, confers resistance to antimycin, and cocrystallization of antimycin with Bos taurus cytochrome b has shown that the analogous Lys227 forms a key bond with antimycin via a water molecule (16,19). In addition, a serine-to-tyrosine substitution at the same position in B. microti was associated with the development of ELQ-271 resistance in vivo (13). The degree of resistance associated with Thr222-Pro is consistent with Q i site inhibition being the primary mechanism of action of ELQ-316.…”
Section: Discussionmentioning
confidence: 99%
“…ELQs are efficacious against malaria, babesiosis, and acute and latent experimental toxoplasmosis (11)(12)(13). Among the large panel of ELQs that we have synthesized, ELQ-316 was found to have the greatest efficacy against T. gondii and did not inhibit human cytochrome bc 1 at concentrations up to 10 M. Previous genetic mutations in Saccharomyces cerevisiae and Plasmodium falciparum suggest that ELQ-271 and ELQ-300, respectively, inhibit the apicomplexan cytochrome bc 1 Q i site (10,12,14).…”
mentioning
confidence: 88%